Analysis Of The Motivation Of Health Workers On The Implementation Of Early Detection Of Growth And Development Of Toddlers - Nur Hasanah Fatimah; Retno Palupi Yonni Siwi; Agusta Dian Ellina; Nita Dwi Astikasari (Journal of Health Science Community, 2024)
Monitoring of the growth and development of toddlers is carried out by health workers who are part of the early detection program for the growth and development of toddlers under the guidance and supervision of the district/city health office. The improvement in the performance of health workers is influenced by motivation in solving all health problems, including the aspect of early detection of the growth and development of toddlers. The motivation of health workers is the main pillar in the world of health services. Motivation will provide energy for health professionals to provide the best service to patients and the community. This study aims to identify the motivation of health workers for the implementation of the early detection program for the growth and development of toddlers at the Kelapa Lima Health Center, Merauke Regency. The type of research used is analytics with a cross sectional approach, free variables are the motivation of health workers and the bound variable is the implementation of early detection of toddler growth and development at the Kelapa Lima Health Center so that this research is carried out in an observational manner, and is a type of correlational analytical research with a cross sectional approach. The Chi-Square statistical test was used to determine the relationship between the two variables. The results of this study are most of the motivation of health workers with a good category and in the implementation of early detection of growth and development with a good category as many as 12 health workers (47.6%) and some of the motivation of health workers with a poor category and in the implementation of early detection of growth and development with a poor category as many as 1 health worker (2.4%). In the chi square test, a significance of 0.005>0.05 was obtained, which can be concluded that there is a relationship between the motivation of health workers and the implementation of early detection of growth and development.